2019
DOI: 10.3390/w11071475
|View full text |Cite
|
Sign up to set email alerts
|

Probability Distributions for a Quantile Mapping Technique for a Bias Correction of Precipitation Data: A Case Study to Precipitation Data Under Climate Change

Abstract: The quantile mapping method is a bias correction method that leads to a good performance in terms of precipitation. Selecting an appropriate probability distribution model is essential for the successful implementation of quantile mapping. Probability distribution models with two shape parameters have proved that they are fit for precipitation modeling because of their flexibility. Hence, the application of a two-shape parameter distribution will improve the performance of the quantile mapping method in the bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(44 citation statements)
references
References 81 publications
(95 reference statements)
1
38
0
5
Order By: Relevance
“…The superior performance of EQM could also be attributable to the adopted monthly approach used in the BC methods application, which takes different precipitation levels into account on individual basis. Various bias correction evaluation studies have also concluded that EQM is typically superior when compared to other BC methods [21,22,32,50,52,53,55,87,[106][107][108]. Contrarily, the distribution-based parametric methods (GQM and GPQM) show slightly larger bias when compared to empirical distributions (EQM), as these methods are based on the assumption that both GCM-RCM and observed data approximate the corresponding theoretical distributions functions [29,35], which could not always be the case for the temporal and spatial precipitation distribution within most climatic regions, especially during the dry season.…”
Section: Jjamentioning
confidence: 99%
“…The superior performance of EQM could also be attributable to the adopted monthly approach used in the BC methods application, which takes different precipitation levels into account on individual basis. Various bias correction evaluation studies have also concluded that EQM is typically superior when compared to other BC methods [21,22,32,50,52,53,55,87,[106][107][108]. Contrarily, the distribution-based parametric methods (GQM and GPQM) show slightly larger bias when compared to empirical distributions (EQM), as these methods are based on the assumption that both GCM-RCM and observed data approximate the corresponding theoretical distributions functions [29,35], which could not always be the case for the temporal and spatial precipitation distribution within most climatic regions, especially during the dry season.…”
Section: Jjamentioning
confidence: 99%
“…A vast number of bias correction procedures are in use, such as the monthly mean correction [20], delta change [21], and quantile mapping [22] techniques. The quantile mapping methods are considered to be the most accurate methods in terms of precipitation [23] among all of the other methods. Therefore, a quantile based bias correction approach was used to adjust for the model biases in this study.…”
Section: Introductionmentioning
confidence: 99%
“…The KMD dataset was therefore corrected using the Quantile Mapping bias correction algorithm technique, which has been widely used for correction of precipitation datasets [57][58][59] and has demonstrated high performances in arid and semi-arid areas [33,60]. In particular, the work of Ringard et al demonstrated its usefulness for satellite-derived datasets correction in scarce observed data contexts [61].…”
Section: Correction Through the Quantile Mapping Methodsmentioning
confidence: 99%